1989
DOI: 10.1002/crat.2170240405
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of CdTe and (Cd, Zn)Te single crystals by a chemical etchant

Abstract: Using a known chemical etchant low‐ and high angle boundaries and lamellar twins can be seen on CdTe and (Cd, Zn)Te crystal ingots as a whole as well as on slices with naked eyes. Also the polarity of {111} samples can be determined in this way. Etch pits are produced on cut and polished surfaces independent of their crystallographic orientation. A new modified etchant was used to study the low angle subgrain structure on (111)Te surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…1-4 and Tables 2 and 3). The electrical properties (carrier density (p), resistivity (r) and [13] 20 ml H 2 O+4 g K 2 Cr 2 O 7 +10 ml HNO 3 +1.5 mg NO 3 Ag (1 1 0) Wermke et al [14] 1HF: 3HNO 3 : 4AgNO 3 1% (1 0 0) Ha¨hnert et al [15] 1{1HF: 1CrO 3 50%: 1ClH}+8H 2 O All the above reported MCT planes. carrier mobility (m)) were evaluated using Hall effect measurements at 77 K, which is the usual operating temperature for detectors (Table 4).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…1-4 and Tables 2 and 3). The electrical properties (carrier density (p), resistivity (r) and [13] 20 ml H 2 O+4 g K 2 Cr 2 O 7 +10 ml HNO 3 +1.5 mg NO 3 Ag (1 1 0) Wermke et al [14] 1HF: 3HNO 3 : 4AgNO 3 1% (1 0 0) Ha¨hnert et al [15] 1{1HF: 1CrO 3 50%: 1ClH}+8H 2 O All the above reported MCT planes. carrier mobility (m)) were evaluated using Hall effect measurements at 77 K, which is the usual operating temperature for detectors (Table 4).…”
Section: Methodsmentioning
confidence: 93%
“…Ha¨hnert for epitaxies [15] and Nakagawa et al [11] and Bagai et al [12], respectively for (1 1 1)Cd and (1 1 1)Te substrates, are reliable chemical etchants. In spite of not being considered as reliable chemical etchants, the Inoue [13] solution for (1 1 0) substrates and Wermke et al [14] solution for (1 0 0) substrates are usually used, since there are no other known etchants for these purposes [20][21][22].…”
Section: Article In Pressmentioning
confidence: 99%
“…Для виявлення міжзеренних границь і двійників, а також ідентифікації полярності поверхні (111) Zn x Cd 1-x Te авторами [16][17][18] запропоновано використовувати розчини складу: 1 HF:3 HNO 3 : 4 (2 %-ого водного розчину AgNO 3 ) (розчин 1); 1 HF: 3 HNO 3 :5 (0,5 %-ого водного розчину AgNO 3 ) (розчин 2). Травлення проводять при кімнатній температурі у розчині 1 впродовж 30 -60 сек., а в розчині 2 -10 -15 сек., причому після обробки…”
Section: вступunclassified